To intermix with our white brothers : Indian mixed bloods in the United States from earliest times to the Indian removals - Ingersoll, Thomas N. (Book collections on Project MUSE., 2005)
The Native Americans of mixed ancestry in 1830 and why Andrew Jackson implemented a law to remove them.